2011
DOI: 10.1007/s11240-011-0008-6
|View full text |Cite
|
Sign up to set email alerts
|

Elicitor-enhanced production of gymnemic acid in cell suspension cultures of Gymnema sylvestre R. Br.

Abstract: Cell suspension cultures of Gymnema sylvestre treated with four different elicitors, methyl jasmonate (MJ), yeast extract, chitin and pectin were studied for the production of gymnemic acid as gymnemagenin equivalent, that was analyzed by high performance liquid chromatography (HPLC). All the four tested elicitors induced gymnemic acid production in cell suspension cultures. Highest gymnemic acid content was achieved following treatment with yeast extract (100.47 ± 0.28 mg/l), this was followed by MJ (70.43 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 65 publications
1
27
0
Order By: Relevance
“…Chitin as b-1,4-linked polymer of N-acetylglucosamine and chitosan (deacetylated chitin) are biotic elicitors extensively studied for their effects on secondary metabolite production in various plant cell cultures (Korsangruang et al 2010;Zhao et al 2010;Lim et al 2013). Pectin as a complex structural polysaccharide composed of b-1,4-linked galacturonic acid subunits was found as effective elicitor in enhancement of plant bioactive compounds in cell suspensions (Wiktorowska et al 2010;Cai et al 2012;Veerashree et al 2012). Dextran describes preparations of D-glucans that contain substantial numbers of 1,6-linked a-D-glucopyranosyl residues.…”
Section: Introductionmentioning
confidence: 99%
“…Chitin as b-1,4-linked polymer of N-acetylglucosamine and chitosan (deacetylated chitin) are biotic elicitors extensively studied for their effects on secondary metabolite production in various plant cell cultures (Korsangruang et al 2010;Zhao et al 2010;Lim et al 2013). Pectin as a complex structural polysaccharide composed of b-1,4-linked galacturonic acid subunits was found as effective elicitor in enhancement of plant bioactive compounds in cell suspensions (Wiktorowska et al 2010;Cai et al 2012;Veerashree et al 2012). Dextran describes preparations of D-glucans that contain substantial numbers of 1,6-linked a-D-glucopyranosyl residues.…”
Section: Introductionmentioning
confidence: 99%
“…Veerashree et al (2012) have reported the elicitation of gymnemic acid through cell suspension cultures by the biotic elicitors such as yeast extract, chitin, pectin and methyl jasmonate. Devi et al (2012) have reported the successful elicitation of gymnemic acid in cell suspension cultures by biotic elicitor, Xanthomonas sp.…”
Section: Resultsmentioning
confidence: 99%
“…Triterpenoid saponins possess a wide range of pharmacological activities including inhibitory activity on glucose absorption (Hideto et al 2006), cholesterol reducing (Gurfinkel and Rao 2003), anticancer, anti-inflammatory and antimicrobial activities (Ridout et al 1991; Netala et al 2015). Yields of triterpenoid saponins have been successfully enhanced in experimental systems by treating the cells and tissues with different biotic and abiotic elicitors (Veerashree et al 2012). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are numerous reports regarding enhancement of gymnemic acid content by different methods such as alteration of macroelements and nitrogen sources of the culture medium (Praveen et al 2011 ), by yeast extract elicitation (Veerashree et al 2012 ), by cadmium chloride elicitation (Bhuvaneswari et al 2012 ) and by blue light treatment (Ahmed et al 2012 ), there is only one available report on the genetic transformation in G. sylvestre which includes A. rhizogenesmediated hairy root cultures and their successful establishment for the increased production of gymnemic acid (Nagella et al 2013 ). A. rhizogenes strain, KCTC 2703, was used to transform different seedling-derived explants, viz.…”
Section: Gymnema Sylvestre R Brmentioning
confidence: 99%